STUDY OF ANTISECRETORY ACTIVITY OF DINITRATE 2-PHENYL-9-DIETHYLAMINOETHYLimidazo[1,2-A] BENZIMIDAZOLE BY METHOD OF CONTINUOUS PERFUSION OF RATS' STOMACHS - M. V. Chernikov; M. A. Oganova; A. S. Gerasimenko; E. A. Artemyev (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2019)
Nowadays, effective pharmacotherapy of acid-dependent gastrointestinal diseases remains an urgent problem of modern gastroenterology. In this regard, the search for new drugs with a pronounced antisecretory activity still continues; their aim is to keep the control over the acid production safe and effective.The aim of this study was an experimental study of the antisecretory activity of the substance and the finished dosage form (FDF) of dinitrate 2-phenyl-9-diethylaminoethylimidazo[1,2-a]benzimidazole.Materials and Methods. The study of antisecretory activity was performed by method of a continuous perfusion of rats' stomachs. The studied substance was administered at the doses of 3, 10 and 30 mg/kg, and the FDF - at the doses of 13 and 26 mg/kg. The substance of Ranitidine (Sigma Аldrich, USA) was used as a reference object in the study of the antisecretory activity of the substance under study, and Ranitidine (Hemofarm A.D., Serbia) was used as a reference drug in the study of the FDF. In order to determine the stimulated secretion immediately before collecting the samples of the perfusate, histamine was administered subcutaneously at the dose of 5 mg/kg. The content of hydrochloric acid in the perfusate was determined by titration of a 0.01 M sodium hydroxide solution. The acidity value was determined in terms of the debit-hour of hydrochloric acid.Results and discussion. The obtained experimental data showed that the studied substance at the dose of 30 mg/kg decreased the basal hydrochloric acid secretion by 54%, which significantly exceeded the antisecretory effect of Ranitidine by 1.8 times. The FDF at the dose of 26 mg/kg, statistically reliable relative to the control and the group treated with Ranitidine, decreased the basal secretion of gastric juice by 33%. The substance at the dose of 30 mg/kg reliably suppressed the stimulated secretion of hydrochloric acid by 80%, while Ranitidine did it by 56%. The FDF at the dose of 26 mg/kg decreased the histamine-stimulated secretion by 66%, and Ranitidine did it by 52%, which was statistically reliable.Сonclusions. The studied substance and its dosage form are more effective in suppressing basal activities and exceed the anisecretory activity of H2 -histamine antagonists of Ranitidine under the conditions of the secretion stimulated by histamine.